THE ANTECEDENT OF SATISFACTION AND ITS IMPACT ON LOYALTY IN IN-PATIENT CARE (STUDY AT XYZ HOSPITAL CIREBON) - Mochamad Deya Najmuddin; Pauline Henriette Pattyranie Tan (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
Patient loyalty is an essential factor contributing to increased in-patient hospital visits. This study aims to understand the importance of patient loyalty in the context of increasing patient visits. This study examines the impact of service quality variables, hospital brand image, patient-perceived value, and patient satisfaction on patient loyalty. This study was conducted in Cirebon City, Indonesia, with 160 eligible samples from state-owned XYZ hospitals. The sample criteria were patients with hospitalization status. Then, this study developed eight hypotheses to examine the statistical connection between direct, intervening, and multiple-effect models. Problem-solving and research emphasis are conducted utilising a numerical technique with a PLS-SEM-based testing tool. The bootstrapping technique is employed alongside the consistent bootstrapping procedure to showcase the findings of hypothesis testing; we discover that the overall hypothesis has a favourable and noteworthy impact.  In testing the importance-performance map analysis (IPMA), it was concluded that the patient's perceived value needs to be improved. In contrast, service quality must be maintained to achieve high patient loyalty.